Prevalence of Hepatitis B among jaundiced cases in paediatric age group - Suman, Sonali; Kumar, Hemant (International Journal of Contemporary Pediatrics, 2020)
Background: Hepatitis B virus (HBV) infection is a global health problem. Over two billion people have been infected with hepatitis B virus globally, of whom over 350 million are chronic carriers. Vertical (mother to child) and horizontal early childhood transmission are the main routes of HBV transmission and are responsible for most chronic infections. The aim of this study was to study the role played by different modes of transmission of HBV and to study the burden of hepatitis B in pediatric age group. Methods: All children below 12 years of age, admitted for jaundice, of both sexes, during one year study period were included. 50 patients (control) who were not suffering from jaundice or known liver disease were also included. Results: Prevalence of HBsAg positivity among jaundiced children was 15.24%. There was increase in HBsAg positivity with increase in the age signifying role of horizontal mode of transmission in Hepatitis B virus infection. Conclusions: HBV infection is an important health problem in paediatric age group. Horizontal mode of transmission plays important role in the spread of HBV infection among children.